VEIN GRAFTS TO LEFT ANTERIOR DESCENDING (LAD) IN EMERGENCY CORONARY ARTERY BYPASS GRAFT (CABG) OF ELDERLY – DOES IT MERIT? - Mehsood, Dawood Kamal; Khan, Muhammad Aamir; Iqbal, Muhammad Afsheen; Janjua, Asif Mehmood; Kiani, Muhammad Rizwan Bashir (Pakistan Armed Forces Medical Journal, 2020)
Objective: To retrospectively analyze 30 days outcome of elderly patients (≥ 70 years) with Acute Coronary Syndrome (ACS) having an indication for emergency CABG within the first 06 hours after onset of symptoms comparing SVG with IMA for grafting LAD artery. Study Design: Descriptive cross sectional study. Place and Duration of Study: Armed Forces Institute of Cardiology / National Institute of Heart Diseases (AFIC/NIHD) Rawalpindi from Jan 2009 to Dec 2013. Patients and Methods: During the study period total 105 patients, who presented with ACS and merited emergency CABG were included in the study. Group I (n=49) received IMA and group II (n=56) received SVG to graft LAD. Primary outcome was mortality and secondary outcome was major complications within 30 days after surgery. Results: Between group I (IMA) and group II (SVG) mortality was 24.49% vs 10.71% respectively (p=0.06). Significant difference was observed between the two groups in maximum Inotropic Score (p=0.049), total inotrope time (p=0.048), total ventilation time (p=0.046), Periop MI (p=0.050), renal replacement therapy (p=0.092), Bleeding (ml) (p=0.007), blood transfusion (p=0.016), Re-opening (p=0.030) and ICU Stay (p=0.055). Conclusion: SVG provides improved survival and lesser complications during 30 days after emergency CABG in elderly as compared to IMA.